Evaluation of the Effectiveness of Corruption Prevention Strategies used by Principals: a Comparative Study of Public Secondary Schools in Nyandarua and Nakuru Counties in Kenya - Ngatia , Richard; Njoka , Johannes; Ndegwa , Lucy (African Journal of Education,Science and Technology (AJEST), 2021)
Many nations around the world assign sizable amount of their budgetary allocation to the education sector, which is sadly plagued by significant avenues for corrupt practices. Corruption in the education sector present difficulties, with considerable negative effects on achievement of a school’s education objectives and development goals of the country. The purpose of this study was to assess the viability of corruption prevention strategies utilized by principals in public secondary schools in Nyandarua and Nakuru Counties in Kenya. The target population comprised of 420 principals. The sample size was computed using Cochran sampling formula which yielded a sample of 321 respondents. Data was gathered through surveys and was analyzed using descriptive and inferential statistics. It was hypothesized that there was no statistically significant difference between the principals’ corruption prevention strategies in Nakuru and Nyandarua Counties in Kenya. Hypothesis testing revealed that the principals’ corruption prevention strategies in Nakuru and Nyandarua Counties were generally the same, and subsequently the null hypothesis (Ho) was accepted. Accordingly, the study inferred that corruption prevention techniques embraced by the principals in public secondary schools in the two counties were the same. The study prescribes the need to upgrade corruption prevention procedures by equipping secondary school principals with abilities and skills to address the problem. This calls for continuous professional training, workshops and courses on prevention of corruption.